Construction of an Automated Removal Robot for the Natural Drying of Cacao Beans - José Tuanama-Aguilar; Carlos Ríos-López; José Luis Pasquel-Reátegui; Carlos Rodríguez-Grández; John C. Santa-Maria; Janina Cotrina-Linares; Cristian García-Estrella; Felix-Armando Fermin-Perez (Sensors)
Cacao producers often obtain low-quality beans due to the poor manual drying process. This study proposes the construction of an automated prototype robot for the removal during natural drying of cacao beans at Cooperativa Agraria Allima Cacao Ltd., Peru, and evaluates its effectiveness on bean quality. The robot comprises three modules (control, displacement, and removal) and motion sensors. Four 400 kg batches were analyzed, obtaining moisture contents of 6.71, 8.59, 7.74, and 6.80% with the robot, compared to 7.86, 7.94, 6.60, and 7.54% with the manual method. The standard deviations in the grains treated with the robot were lower, evidencing a more uniform drying. In addition, the total phenol content was higher in the robot-dried beans, indicating better preservation of bioactive compounds. Although the robot did not reduce the drying time, we conclude that its sustainable and economically accessible design contributed to obtaining higher-quality beans compared to the conventional method, with more homogeneous drying and better preservation of phenols, key aspects for producing high-quality cacao.